O2 Prevalence of ankle sprain and instability among rural high school students - Holland, BB; Needle, AR; Battista, RA; Christiana, RW (British journal of sports medicine, 2017)
Study DesignCross-sectional.ObjectivesTo quantify the prevalence of ankle sprain among a population of rural high school students.BackgroundThe healthcare burden of ankle sprains and their sequelae have been highlighted, largely due to the substantial volume of injuries observed. Although injury rates are frequently presented, a paucity of evidence exists describing the prevalence of ankle sprain and instability among high school-aged students.Methods and MeasuresA survey was distributed via electronic mail to students at a high school in northwestern North Carolina. Participating students provided demographic information and answered questions regarding their ankle injury history, and completed instruments including the Identification of Functional Ankle Instability (IdFAI), Foot and Ankle Ability Measure (FAAM) with sport subscale, and Disablement in the Physically Active (DPA). Differences in FAAM, FAAM-sport, and DPA subscales were compared with Student’s t-tests between previously injured and uninjured subjects (α=0.05).Results201 students completed the survey. 115 respondents (57.2%) indicated a history of ankle sprain (Males 56.3%; Females 58.3%). Of those indicating sprain history, 40 individuals (19.9%) reported a history of injury within the past year, while among those more than a year from injury, 59 respondents (78.6%) reported chronic ankle instability (IdFAI ≥11), and 16 respondents (21.3%) met criteria of ankle copers (IdFAI ≤10). Pearson’s chi-squared revealed no significant differences in frequency of injury across ages (χ2=0.18, p=0.27). No significant differences were observed between FAAM (t147=1.52, p=0.13), FAAM-sport (t148=0.19, p=0.85), or DPA (t150=0.62, p=0.54) between injured and uninjured respondents.ConclusionPrevalence of ankle sprain history in a rural high school population is consistent with injury rates observed among college students and the general population, despite age differences. The rates of chronic ankle instability in this population is notably higher than previously reported in literature, suggesting the potential importance of interventions among this population.